1996
DOI: 10.1152/ajpendo.1996.270.6.e961
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of epinephrine on muscle proteolysis in perfused rat hindquarters

Abstract: An acute and direct effect of epinephrine (Epi) on muscle proteolysis was investigated using a single-pass mode of rat hindquarter perfusion. The rate of tyrosine (Tyr) release at > 30 min with cycloheximide was regarded as the muscle proteolytic rate. Infusion of Epi (500 nM) to the hindquarters of fed rats led to a sharp decrease in the Tyr release to 50% within 5 min, accompanied by an increase in perfusion pressure and edema around the perfused tissues. To clarify the mechanism, alpha- and beta-antagonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The data of the present work clearly show that catecholamines exert an inhibitory action on proteolysis in rat isolated skeletal muscle. The epinephrine-induced reduction in the rate of protein breakdown in isolated muscles (ϳ15-20%) was similar to that observed after epinephrine infusion in humans (30), in rat perfused hindlimb (11), and in muscle microdialysis experiments (28). An inhibitory action of catecholamines on skeletal muscle proteolysis was also suggested in a recent study from this laboratory (20) showing that rates of protein degradation in isolated muscles increase after acute chemical sympathectomy induced by guanethidine.…”
Section: Effect Of Dbcamp and Ibmx On Muscle Proteolysissupporting
confidence: 78%
“…The data of the present work clearly show that catecholamines exert an inhibitory action on proteolysis in rat isolated skeletal muscle. The epinephrine-induced reduction in the rate of protein breakdown in isolated muscles (ϳ15-20%) was similar to that observed after epinephrine infusion in humans (30), in rat perfused hindlimb (11), and in muscle microdialysis experiments (28). An inhibitory action of catecholamines on skeletal muscle proteolysis was also suggested in a recent study from this laboratory (20) showing that rates of protein degradation in isolated muscles increase after acute chemical sympathectomy induced by guanethidine.…”
Section: Effect Of Dbcamp and Ibmx On Muscle Proteolysissupporting
confidence: 78%
“…In agreement with this suggestion, we have found that both epinephrine and norepinephrine, added in vitro, reduce the rate of protein degradation in normal rat soleus and extensor digitorum longus (EDL) by approximately 15-20% (15). This view is consistent with the finding that infusion of epinephrine in muscle microdialysis experiments (16), in perfused rat hindquarters (17) and in humans (18) induces a rapid and similar 20% decrease in protein degradation.…”
Section: Introductionsupporting
confidence: 91%
“…36). Some of these have been based on ex vivo proteolysis experiments performed with prepubertal rat muscles (12,26,28,32,37,47,50). Here we found that ␤-adrenergic agonists isoproterenol (nonselective) and formoterol (␤ 2 -selective) also reduced proteolysis of adult rat skeletal muscle by 12-20%.…”
Section: Discussionmentioning
confidence: 57%